A Analysis of Price to Book Value Determinants: The Role of ROE, DER, and Firm Size in the BEI Miscellaneous Industry Sector (2020-2024) - W, Dwi Perwitasari; Sibarani, Elisabeth Fransiska; Arifin, Salahuddin Rijal (Growth, 2025)
This study reveals that return on equity (ROE) significantly increases price to book value (PBV), while debt to equity ratio (DER) and firm size do not show a significant effect. A comprehensive analysis proves that these three factors together influence company valuation, with profitability emerging as the main determining factor. These findings reinforce the importance of financial performance in market valuation, while capital structure and operational scale show a more limited impact. Keywords: return on equity, debt to equity rasio, firm size, price to book value